Complex Role of Collybistin and Gephyrin in GABA(A) Receptor Clustering - Saiepour, Leila (American Society for Biochemistry and Molecular Biology, 2010)
Gephyrin and collybistin are key components of GABA(A) receptor (GABA(A)R) clustering. Nonetheless, resolving the molecular interactions between the plethora of GABA(A)R subunits and these clustering proteins is a significant challenge. We report a direct interaction of GABA(A)R α2 and α3 subunit intracellular M3–M4 domain (but not α1, α4, α5, α6, β1–3, or γ1–3) with gephyrin. Curiously, GABA(A)R α2, but not α3, binds to both gephyrin and collybistin using overlapping sites. The reciprocal binding sites on gephyrin for collybistin and GABA(A)R α2 also overlap at the start of the gephyrin E domain. This suggests that although GABA(A)R α3 interacts with gephyrin, GABA(A)R α2, collybistin, and gephyrin form a trimeric complex. In support of this proposal, tri-hybrid interactions between GABA(A)R α2 and collybistin or GABA(A)R α2 and gephyrin are strengthened in the presence of gephyrin or collybistin, respectively. Collybistin and gephyrin also compete for binding to GABA(A)R α2 in co-immunoprecipitation experiments and co-localize in transfected cells in both intracellular and submembrane aggregates. Interestingly, GABA(A)R α2 is capable of “activating ” collybistin isoforms harboring the regulatory SH3 domain, enabling targeting of gephyrin to the submembrane aggregates. The GABA(A)R α2-collybistin interaction was disrupted by a pathogenic mutation in the collybistin SH3 domain (p.G55A) that causes X-linked intellectual disability and seizures by disrupting GABA(A)R and gephyrin clustering. Because immunohistochemistry in retina revealed a preferential co-localization of collybistin with α2 subunit containing GABA(A)Rs, but not GlyRs or other GABA(A)R subtypes, we propose that the collybistin-gephyrin complex has an intimate role in the clustering of GABA(A)Rs containing the α2 subunit.